The Effects of Social Media on the Mental Health of Malaysian University Students: A Review - Thangaveloo, Aneshkumar; Chetiyar, Saralah Devi Mariamdaran (Journal of Mental Health and Social Rehabilitation, 2024)
their students, which has stimulated interest in its effects on mental health. In this review, it would envisage to look and review the existing body of literature related to the relationship between social media usage and mental health particularly among Malaysian university students. The review collates results from a number of studies that examine the impact of social media on mental health, including social media addiction, anxiety, depression, and self-esteem. This paper looks at the positive and negative impacts of social media use and how the impact of using social media can vary depending on individual, cultural, and educational context in Malaysia. Positive outcomes noted are increased social connectivity, emotional support, learning and self-expression while negative consequences include the rise of mental health issues like increased isolation, anxiety, low self-esteem sometimes compounded by overuse and problematic social media behavior. In addition, the review examines the degree social media use has on the mental wellbeing of Malaysian students, and the extent to which cultural and educational factors influence how social media use impacts mental wellbeing. Finally, the review suggests directions for future research, especially the need for longitudinal studies to understand better the long-term effects of social media use on mental health. Also, we provide practical recommendations, including promoting awareness of healthy social media habits, university led initiatives to encourage balanced use, and support to mental health resources for students who may experience social media related challenges